2020
DOI: 10.21203/rs.3.rs-96621/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Machine Learning Model to Predict Death Outcome in Severe COVID-19 Patients

Abstract: BackgroundThe novel coronavirus disease 2019 (COVID-19) spreads rapidly among people and causes a global pandemic. It is of great clinical significance to identify COVID-19 patients with high risk of death.MethodsA total of 2,169 adult COVID-19 patients were enrolled from Wuhan, China between February 10th and April 15th, 2020. Difference analyses of medical records were performed between severe and non-severe groups as well as between survivors and non-survivors. In addition, we developed a decision tree clas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…Thus, like Li et al (2020), we observed a considerable reach of YouTube as a form of communication with the public, but a critical view regarding the information about COVID-19 found on YouTube is needed.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Thus, like Li et al (2020), we observed a considerable reach of YouTube as a form of communication with the public, but a critical view regarding the information about COVID-19 found on YouTube is needed.…”
Section: Discussionmentioning
confidence: 52%
“…Li et al (2020) conducted a survey on YouTube on March 21, 2020, using the keywords "coronavirus" and "COVID-19" and analyzed the 75 most viewed videos resulting from each search. Videos that were duplicate, non-English language, non-audio, non-visual, longer than 1 hour, live, and unrelated to COVID-19 were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations